PENGARUH PENERAPAN SISTEM E-FILING, SANKSI PAJAK, DAN PEMAHAMAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Malau, Siska Permatasari; Ismanto , Juli (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to analyze the influence of the e-filing system, tax sanctions, and taxpayer understanding. This study was conducted by analyzing taxpayer compliance at KPP Pratama Pondok Aren. The sample used in this study was determined by the slovin formula using convenience sampling techniques. The data used in this study are primary data in the form of distributing questionnaires to all taxpayers at KPP Pratama Pondok Aren. The variables used in this study are the E-filing System, Tax Sanctions, and Taxpayer Understanding and Taxpayer Compliance. The multiple regression method is used as the research methodology in this study. Analysis of the research results using SPSS assistance. The partial results of the study indicate that the e-filing system has a significant effect on taxpayer compliance. Taxpayer understanding also does not have a significant effect on taxpayer compliance. In addition, there are other variables that affect taxpayer compliance that cannot be explained in this study.